Implementation of quality function deployment to identify priority needs of customers and health providers of child-friendly community health centre - Ni Nyoman Ariani; Ni Made Sri Nopiyani; I Putu Ganda Wijaya (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: The efforts to increase quality of service is critical in public services. Service providers should be able to identify customer needs and expectations. As one of health providers, community health centre are required to develop mechanisms for identifying needs of customers and staff. Needs assessment of clients and staff at Blahbatuh II Health Centre is never been conducted. This study aims to identify priority needs of customer and staff to improve the quality of service at Blahbatuh II Health Centre. Methods: A quantitative study was conducted at Blahbatuh II Health Centre. Data was collected through interviews guided by a structured questionnaire. A total of 97 customers were consecutively selected and were interviewed. Eight staff of child-friendly community health centres were purposively recruited. Data was analysed using quality function deployment method and presented in the House of Quality (HoQ) matrix. Results: There were 16 and 13 expectations from customers and staff respectively. The house of quality matrix showed that respondents ranked several expectations as the most important that include friendly staff, quick and on-time services, and effective treatment. Health staff on the other hand expected the centre to implement performance-based reward system, to provide training program and to follow the standard operating procedures. Conclusions: Expectations from customers and health staff are different. In order to meet these expectations, health centre should design and implement a quality improvement program to address these diverse quality issues.